Consumption Aspects that Create Life Satisfaction - LEELAKULTHANIT, Orose (Journal of Environmental Management and Tourism, 2020)
Consumption is one of the main activities in life. Given the many aspects of this activity, it is the interest of this study to investigate the contribution of these aspects of consumption on life satisfaction. These consumption aspects include quality products, fair prices, easily accessible products, promotions, time-saving products, luxury products, eco-friendly products, new technology products, and consumption expenditure. A total of 450 responses were collected from adult shoppers in Bangkok, Thailand. The results of the multiple regression analysis indicated that among the various aspects of consumption, time-saving products was the sole determinant of people’s life satisfaction. In addition, age and household income were two other demographic variables that were seen to have a positive effect on a person’s life satisfaction. Regarding the high household income group, consumption expenditure and age were positively related to life satisfaction.